2021
DOI: 10.3389/fmolb.2020.614034
|View full text |Cite
|
Sign up to set email alerts
|

CLEC3B as a Potential Prognostic Biomarker in Hepatocellular Carcinoma

Abstract: C-Type Lectin Domain Family 3 Member B (CLEC3B) encodes proteins associated with tumor invasion and metastasis. However, the interrelation between CLEC3B gene expression, tumor immunity, and prognosis of patients with hepatocellular carcinoma (HCC) is unclear. This study was conducted to investigate the prognostic potential of CLEC3B and its association with tumor tissue infiltration markers. CLEC3B expression was examined using the TIMER and Oncomine databases, with its prognostic potential assessed using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Matsumoto et al [ 46 ] revealed that inhibition of PFKFB3 suppressed tumor growth and induced tumor vascular normalization in HCC. CLEC3B, a member of the C-type lectin superfamily, has been reported to be downregulated in serum and tumor tissues of HCC [ 48 , 49 ]. Dai et al [ 48 ] found that downregulation of exosomal CLEC3B in HCC promoted metastasis and angiogenesis through AMPK and VEGF signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Matsumoto et al [ 46 ] revealed that inhibition of PFKFB3 suppressed tumor growth and induced tumor vascular normalization in HCC. CLEC3B, a member of the C-type lectin superfamily, has been reported to be downregulated in serum and tumor tissues of HCC [ 48 , 49 ]. Dai et al [ 48 ] found that downregulation of exosomal CLEC3B in HCC promoted metastasis and angiogenesis through AMPK and VEGF signaling.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, people have increasingly realized the role of the immune system in the occurrence and development of cancer, and at the same time, tumor immunotherapy has developed rapidly ( Xie et al, 2021 ). Both sufficient immune cells infiltrate the tumor microenvironment and adequate expression of immune checkpoints were required for tumor immunotherapy to achieve curative effect ( Chae et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oncomine (https://www.oncomine.org/resource/login. html) is currently the world's largest cancer-related gene microarray database and integrated data-mining platform, collecting the most complete spectrum of cancer mutations, associated gene expression profiles, and relevant clinical information (22). In this study, we selected the CALCRL gene as the subject and compared its expression levels in tumor tissues and normal tissues.…”
Section: Oncomine Database Analysismentioning
confidence: 99%